2020
DOI: 10.1371/journal.pone.0226976
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 paralogs and the risk of unselected breast cancer: A case-control study

Abstract: A case-control study was conducted in which we evaluated the association between genetic variability of DNA repair proteins belonging to the Rad51 family and breast cancer (BrC) risk. In the study, 132 female BrC cases and 189 healthy control females were genotyped for a total of 14 common single nucleotide polymorphisms (SNPs) within Rad51 and Xrcc3. Moreover, our previously reported Rad51C genetic data were involved to explore the nonlinear interactions among SNPs within the three genes and effect of such in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Studies have shown multiple altered variants in DNA repair genes implied in BC predisposition, development, and outcome [ 11 , 12 , 13 , 14 ], including BRCA and non-BRCA genes. Among these, pathogenic variants in the high penetrance BRCA1/2 genes account for 50–60% and the remaining variants, to non-BRCA genes of moderate and low penetrance, including ATM , PALB2 , RAD51 , and BARD1 , all involved in double-strand break repair pathways [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For this reason, it is relevant to elucidate the mechanisms of DNA repair genes in BC, using different approaches such as in silico, in vitro, and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown multiple altered variants in DNA repair genes implied in BC predisposition, development, and outcome [ 11 , 12 , 13 , 14 ], including BRCA and non-BRCA genes. Among these, pathogenic variants in the high penetrance BRCA1/2 genes account for 50–60% and the remaining variants, to non-BRCA genes of moderate and low penetrance, including ATM , PALB2 , RAD51 , and BARD1 , all involved in double-strand break repair pathways [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For this reason, it is relevant to elucidate the mechanisms of DNA repair genes in BC, using different approaches such as in silico, in vitro, and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…XRCC3 rs861539 (p.Thr241Met) is a non-synonymous SNP in the ATP-binding domain of the protein that affects XRCC3 interactions with other proteins [ 43 ]. Several studies investigated the role of this SNP in response to RT in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…19 studies including 13 countries) [44], Polish [40], and European [22] women. We also observed that the mutant CC genotype elevated the risk of metastasis in individuals with the homozygous mutant genotype.…”
Section: Plos Onementioning
confidence: 99%
“…Last decade, there have been conflicting reports regarding the impact of the HRR gene polymorphisms on BC risk [20][21][22][23][24][25][26]. Besides, there is a paucity of information regarding the impact of HRR gene polymorphisms on South Indian women's BC etiology.…”
Section: Introductionmentioning
confidence: 99%